Temperature Modulation and Feed Supplementation Significantly Improve Population Growth of Laboratory‐Reared Dero digitata (Annelida: Naididae). (13th July 2021) - Tiwari, Ambika; Woodyard, Ethan T.; Rosser, T. Graham; Griffin, Matt J.; Mischke, Charles C.
Abstract: Dero digitata is the definitive oligochaete host of Henneguya ictaluri (Cnidaria: Myxobolidae), the causative agent of proliferative gill disease in U.S. farm‐raised Channel Catfish Ictalurus punctatus and hybrid catfish (Channel Catfish × Blue Catfish I. furcatus ). Several studies were performed to identify optimal conditions for culturing D. digitata in the laboratory for experimental life cycle studies. The first experiments investigated the effects of temperature on D. digitata population growth. Five different growth studies were conducted, each consisting of three different temperature treatments ranging from 7°C to 32°C. Cultures were held under different temperature regimes, and D. digitata numbers were determined after 2 weeks. Dero digitata populations reared at 21–32°C had significantly higher population growth than those maintained at lower temperatures. Additional experiments investigated the effects of supplemental diets on laboratory‐reared D. digitata populations. Treatments consisted of autoclaved water that was collected from production ponds with substantial algal growth or a reservoir pond with a negligible algal bloom and maintained at ideal temperatures determined from the temperature trials ( 26°C). Cultures were supplemented with three different commercially available feeds designed for bottom‐feeding ornamental fish. Significantly larger numbers and greater reproductive rates, taken as an indirect measure of population fitness, were observed in D. digitata cultured in autoclaved pond water supplemented with algal wafers containing 29.0% minimum (min.) crude protein, 7.0% min. crude fat, 6.0% maximum (max.) crude fiber, 9.0% max. moisture, and 0.8% min. phosphorus. A final experiment showed that weekly water exchanges resulted in greater population growth of D. digitata relative to culture in nonexchanged water. This work optimizes the laboratory propagation of D. digitata and will facilitate life cycle studies and controlled experiments establishing developmental timelines and host–parasite interactions of H. ictaluri, similar to other myxozoan parasites.